Knowledge Level of Community Participant on Dengue Fever Symptoms and Early Treatment in Bandung City - Lia Faridah; Nisa Fauziah; Savira Ekawardhani (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2019)
In tropical countries, dengue fever is often confused with other common tropical infections. There are no specific therapeutic treatment for dengue infections, and the key of successful dengue case management are a timely and judicious supportive care. Community knowledge about dengue fever and treatment at home, particularly for children is crucial to reduce the burden of dengue infection. Unfortunately, studies on community's knowledge of dengue fever are still very limited. The aims of this study are to measure people's knowledge about dengue fever and to determine the main predictors of a high index on dengue knowledge, in Bandung City. Data collection was carried out by interviewing respondents from each household. Multivariate analysis with logistic regression was used to determine the odds-ratio demographic factors that reached a high index. Study participants generally showed medium-to-high level of knowledge regarding Dengue fever symptoms and its first aid. This group accounts for more than 70% of all respondents This study also showed that the likeliness of having high-score of knowledge was correlated with being a female, having at least an undergraduate level of education, and being an entrepreneur